Pengaruh Content Marketing dan SEO (Search Engine Optimization) Terhadap Keputusan Pembelian Melalui Minat Beli: Studi pada Konsumen Produk UKM F&B di Kabupaten Pasuruan - Indah Zanubah Khafsoh; Miftahul Huda (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze the relationship between Content Marketing and Search Engine Optimization (SEO) on Purchase Decisions through Buying Interest in consumers of F&B SME products in Pasuruan Regency. This study uses an explanatory research approach with data analysis techniques using path analysis. The type of data used is quantitative data, using questionnaires as a data source. The sampling method uses purposive sampling with certain criteria. The results of this study show that: 1) The Content Marketing variable has a significant effect on the Buying Interest variable with a t-calculated value of 3.811 > 1980. 2) The Search Engine Optimization (SEO) variable has a significant effect on the Buying Interest variable with a t-count value of 7.672 > 1980. 3) The Content Marketing variable has a significant effect on the Purchase Decision variable with a t-calculated value of 3.126 > 1980. 4) The Search Engine Optimization (SEO) variable has a significant effect on the Purchase Decision variable with a t-count value of 3.841 > 1980. 5) the Buying Interest variable has a significant effect on the Purchase Decision variable with a t-calculated value of 5.439 > 1980. 6) The Content Marketing variable has a significant effect on the Purchase Decision variable through the Buying Interest variable with a t-calculated value of 3.807 > 1980. and 7) The Search Engine Optimization (SEO) variable has a significant effect on the Purchase Decision variable through the Buying Interest variable with a t-count value of 4,900 > 1980.